2020
DOI: 10.1152/ajpcell.00039.2020
|View full text |Cite
|
Sign up to set email alerts
|

Osteoclast-derived exosomal let-7a-5p targets Smad2 to promote the hypertrophic differentiation of chondrocytes

Abstract: The invasion of osteoclasts into the cartilage via blood vessels advances the process of endochondral ossification, and dysregulation of dynamic intercellular interactions results in skeletal dysplasias. Although the regulation of osteoclasts by growth plate chondrocytes has been reported in detail, the effect of osteoclasts on chondrocytes remains to be determined. In this study, ATDC5 cells and bone marrow mesenchymal stem cells were differentiated into chondrocytes and treated with conditioned medium obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 54 publications
(40 reference statements)
0
22
0
Order By: Relevance
“…Osteoclasts at distinct stages of differentiation derived from bone marrow mononuclear cells (BMMCs) may affect the normal phenotype of chondrocytes. Our group reported that exosomal let-7a-5p from preosteoclasts and mature osteoclasts targets Smad2 to promote the hypertrophic differentiation of chondrocytes, 75 providing insights into ‘OC–CC coupling’ during OA progression.…”
Section: Regulation Feedback Loop Of ‘Osteoclast–chondrocyte Crosstalmentioning
confidence: 99%
“…Osteoclasts at distinct stages of differentiation derived from bone marrow mononuclear cells (BMMCs) may affect the normal phenotype of chondrocytes. Our group reported that exosomal let-7a-5p from preosteoclasts and mature osteoclasts targets Smad2 to promote the hypertrophic differentiation of chondrocytes, 75 providing insights into ‘OC–CC coupling’ during OA progression.…”
Section: Regulation Feedback Loop Of ‘Osteoclast–chondrocyte Crosstalmentioning
confidence: 99%
“…Similarly, exosomes derived from RANKL-induced, osteoclastic RAW 264.7 cells contain miR-23a-5p that downregulates Runx2, an essential transcription factor for bone formation [123], to inhibit osteogenic differentiation [124]. Osteoclast-derived exosomes also contain let-7a-5p, which targets the SMAD2/TGFB-induced pathway to inhibit chondrogenic differentiation and therefore promotes hypertrophic differentiation of chondrocytes [125]. Thus, it remains an exciting possibility that osteoclast-derived exosomes, which possess targeting for osteoprogenitors, may be loaded with anabolic miRNAs for therapeutic purposes to drive osteogenic responses.…”
Section: Osteoclast-secreted Evsmentioning
confidence: 99%
“…Slightly more is known about systemically-derived EVs that target osteoclasts to influence the regulation of bone mass. Many of these miRNA-containing exosomes originate from tumor cells from various sources, and are often called "tumor-derived exosomes", which can influence various aspects of osteoclastic activity, depending on their particular target mRNAs [126]. These miRNA-containing exosomes arise from diverse sources including breast cancer cells [127], prostate cancer cells [77,128], multiple myeloma plasma cells [129][130][131], osteosarcoma cells [132] and lung adenocarcinoma cells [133].…”
Section: Systemically-derived Evs Affecting Osteoclastsmentioning
confidence: 99%
“…The exosome sample was diluted 1:100 in PBS, and 1000 μl of diluted sample was injected into the sample tank, and the sample was pressurized to pass through the nanopore at a uniform speed and analyzed by the software. The characteristic proteins, TSG101 and CD63, were detected through western blotting 14,24 …”
Section: Methodsmentioning
confidence: 99%